ANALISIS KATA TIDAK BAKU PADA KARANGAN ILMIAH SISWA KELAS XI SMA NEGERI 1 MEUREUBO KABUPATEN ACEH BARAT - Syafrizal, Syafrizal (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
This research is entitled "Analysis of Non-Standard Words in Scientific Essays of Grade XI Students of SMA Negeri 1 Meureubo, West Aceh Regency". The problem in this study is how to use non-standard words in the scientific essays of grade XI students of SMA Negeri 1 Meureubo, West Aceh Regency. This study aims to describe the use of non-standard words in the scientific essays of grade XI students of SMA Negeri 1 Meureub, West Aceh Regency. The population of this study is grade XI students of SMA Negeri 1 Meureubo. The source of data for this research is student papers and reports on the results of observations or observations. The method used is a descriptive-qualitative method. Data collection was carried out using documentation techniques. Based on the results of the research obtained, there are still non-standard words in the scientific essays of grade XI students of SMA Negeri 1 Meureubo. The source of data for this research is student papers and reports on the results of observations or observations. The method used is a descriptive-qualitative method. Data collection was carried out using documentation techniques. Based on the results of the research obtained, there are still non-standard words in the scientific essays of grade XI students of SMA Negeri 1 Meureubo. The inconsistency of these words is caused by several factors, namely the factor of error in writing basic words, the factor of errors in the writing of suffix words, the factor of incorrect use of capital letters, and the factor of inconsistency in word abbreviation. These factors, when presented, are obtained as follows. The root word writing error factor was 15.66%. The factor of error in writing affixes is 26.50%. The factor of misuse of capital letters was 7.01%, and the factor of inaccuracy of word abbreviation was 6.04%. From the results of the analysis obtained, it can be concluded that grade XI students of SMA Negeri 1 Meureubo are still unable to master standard vocabulary or still have a low understanding of the materials presented by Indonesian language teachers.